2019
DOI: 10.1016/j.ijscr.2019.07.070
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular osteoid osteoma of tempromandibular joint: A case report

Abstract: Highlights Osteoid osteoma is a benign bone neoplasm, with significant nocturnal pain that responds to NSAIDs. A case of an intra-articular osteoid osteoma involving the articular eminence and glenoid fossa of TMJ in a 46-years-old female is reported. CT scan imaging is helpful in displaying the typical radiographic features and localization of the lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…First described by Jaffe in 1935, osteoid osteoma is a benign osteoblastic tumor, not related to an infectious phenomenon. It frequently develops in long bones, but it very rarely occurs in the head and neck [ 7 ]. A review of the literature was carried out from the MEDLINE database via PubMed interface.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…First described by Jaffe in 1935, osteoid osteoma is a benign osteoblastic tumor, not related to an infectious phenomenon. It frequently develops in long bones, but it very rarely occurs in the head and neck [ 7 ]. A review of the literature was carried out from the MEDLINE database via PubMed interface.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike osteoid osteoma, osteoblastoma has a larger size of >2 cm and up to 10 cm in aggressive patterns. They do not manifest surrounding reactive osteosclerosis, with the medullary bone of axial skeleton being affected in the majority of cases [ 7 ]. Besides, it is reported that osteoid osteoma does not recur after complete removal of the nidus, whereas recurrence of osteoblastoma after complete resection is reported in several cases [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Na ATM, na maioria dos casos relatados, a lesão envolve a cabeça do côndilo Research, Society and Development, v. 9, n. 10, e7139109104, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i10.9104 mandibular. Dependendo dos sintomas, o tratamento varia de medidas conservadoras, como o tratamento com AINES, a procedimentos mais invasivos, como a excisão cirúrgica, que pode trazer alívio imediato da dor (Issa et al, 2019).…”
Section: Osteomasunclassified